COVID-19 misinformation in anti-vaccination websites: a content analysis of archived websites - von Isenburg, Megan; Waldrop, Lucy B.; Kaplan, Samantha (2023)
This session will provide an overview of a content analysis conducted on archived anti-vaccination websites, specifically describing how pre-existing anti-vaccination websites presented information about COVID-19. We will also address the use of Archive-It, a common web archiving tool, for capturing transient web information and misinformation for research purposes. The content analysis was conducted on a collection of 25 anti-vaccination websites established by the IvyPlus Web Collection Program prior to the pandemic and crawled every 6 months via Archive-It. Websites were assessed for anti-vaccination themes and misinformation techniques. The majority of websites addressed COVID-19 vaccines in a negative fashion, with more websites making appeals to personal freedom or expressing skepticism of science than questioning safety. Many sites appropriated standard web markers of legitimacy. We also assessed the strengths and limitations of using archived websites in the context of web and misinformation research. The archived versions of the websites had significant shortcomings, particularly in search functionality, and required supplementation with the live websites.